Faktor - Faktor yang Mempengaruhi Pemilihan Kontrasepsi Non MKJP pada PUS - Jenie Palupi; Syiska Atik Maryanti; Ida Prijatni; Aisyah Zahroh Wahidiyah (ARTERI : Jurnal Ilmu Kesehatan, 2023)
The family planning program is the most basic preventive health effort for women. Based on data from the East Java Provincial Health Office in 2017, 77.1% of new family planning acceptors and active family planning acceptors used non-MJKP contraception, while 23% used MJKP contraception.The high number of non-MKJP contraceptive acceptors is caused by several factors including age, education level, number of children, husband's support. This study aims to determine the factors that influence the selection of Non-MKJP contraception in the Tapen Puskesmas District of Bondowoso. This study is a comparative study with a cross sectional approach, using Simple Random Sampling with a sample consisting of 110 Non MKJP contraceptive acceptors. The instrument used was a questionnaire. Data were analyzed using chi-square. The results obtained 69.1% of mothers with a healthy reproductive age category, mothers at the Senior High School (SMA) education level of 55.5%, mothers who had 2 children were 51.8%, and those who received husband's support were 80.0 %. Data were analyzed by chi-square test. The results of the bivariate analysis showed that the age factor showed (p = 0,000), education level (p = 0,000), number of children (p = 0,000), husband's support (p = 0,000). The α value of the four factors is 0.05. Age, education level, number of children, husband's support are influenced by the high number of non-MKJP contraceptive acceptors in the work area of ​​Tapen Puskesmas, Bondowoso Regency. Government efforts have been good in suppressing birth rates by providing information about Non-MKJP contraception and making the Non-MKJP contraceptive method as one of the methods that is quite effective and able to help the success of government programs especially in the field of KB Keywords: Contraception acceptors, MKJP, Fertile Age Couples (PUS)